Developmental administration of valproic acid alters DNA methylation and maternal behavior. Issue 3 (14th March 2022) - Collins, Nicholas J.; Zimmerman, Catherine W.; Phillips, Natalia L. H.; Fern, Samantha; Doherty, Tiffany S.; Roth, Tania L.
Abstract: Exposure to adversity in early development has powerful and potentially lasting consequences on behavior. Previous work in our laboratory using female Long‐Evans rats has demonstrated that exposure to early‐life maltreatment manifests into alterations in dam behavior, including a perpetuation of the maltreatment phenotype. These observed behavioral changes coincide with changes in epigenetic activity in the prefrontal cortex (PFC). Further, treating dams with a chromatin modifying agent (Zebularine) normalizes methylation and maltreatment phenotypes, suggesting a link between epigenetic programming and phenotypic outcomes. Here, we sought to investigate if administration of a chromatin modifying agent concurrent with the experience of maltreatment normalizes epigenetic activity associated with maltreatment and alters behavioral trajectories. Administration of valproic acid (VPA) transiently lowered levels of global DNA methylation in the PFC, regardless of exposure to nurturing care or maltreatment. When VPA‐exposed animals reached adulthood, they engaged in more adverse behaviors toward their offspring. These data provide further evidence linking epigenetic changes in the developing brain with effects on behavior.